2009
DOI: 10.1007/s00253-009-2012-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus plantarum MA2 isolated from Tibet kefir on lipid metabolism and intestinal microflora of rats fed on high-cholesterol diet

Abstract: The objective of this study was to evaluate the effects of Lactobacillus plantarum MA2, an isolate from Chinese traditional Tibet kefir, on cholesterol-lowering and microflora of rat in vivo. Rats were fed on cholesterol-enriched experimental diet, supplemented with lyophilized L. plantarum MA2 powder, with a dose of 10(11) cells/day per mice. The results showed that L. plantarum MA2 feeding significantly lowered serum total cholesterol, low-density lipoprotein cholesterol, and triglycerides level, while there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
98
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(127 citation statements)
references
References 42 publications
16
98
0
12
Order By: Relevance
“…The strain used in this study had previously shown good survival in conditions simulating normal exposure to stomach acidity as well as high bile salt concentrations and additionally large bowel colonization can be inferred from the high counts of lactobacilli in the test group compared to the control group. The lactobacilli count increased steadily with time in the course of the study in agreement with several studies where administration of lactobacilli is positively correlated with significantly higher fecal lactobacilli counts [13,15,23]. In these studies the control is usually stable as in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The strain used in this study had previously shown good survival in conditions simulating normal exposure to stomach acidity as well as high bile salt concentrations and additionally large bowel colonization can be inferred from the high counts of lactobacilli in the test group compared to the control group. The lactobacilli count increased steadily with time in the course of the study in agreement with several studies where administration of lactobacilli is positively correlated with significantly higher fecal lactobacilli counts [13,15,23]. In these studies the control is usually stable as in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…In their study, the total cholesterol, triglycerides and low-density lipoprotein cholesterol levels of mice in the control group were found to be significantly higher. Similar results were reported by Huang et al [24] and Wang et al [13] from studies on cholesterol-lowering effects of L. plantarum strains isolated from Tibetan kefir grains. Huang et al [24] found that their isolate significantly lowered serum total cholesterol, low-density lipoprotein cholesterol, and triglycerides concentrations but not serum high-density lipoprotein cholesterol concentrations and furthermore [23] indicating that these effects are not limited to a few species.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations